On the contradictions of activation policies for professional social work - 'welcome visits for new-borns' in the framework of early childhood intervention - Hannah Kristin Dehm (Social Work and Society)
Quite often, efforts to theorize the relationship between social policy and social work critically turn out to be deterministic: if there are changes in the socio-political logic, this will lead to a corresponding change in social work. With reference to theoretical approaches developed in the context of 'regulation theory' and its neo-Marxist concept of the state, this paper suggests a different approach by reformulating the relationship as contradictory. The resulting ambivalent character of social work - specifically in the context of the German activating state - will be exemplified by the so-called welcome visits for newborns, a service within the field of early childhood intervention. This field has been established over the last fifteen years as being influenced by, among other things, social investment strategies in the context of the activating state. This paper will examine to what extent activation strategies reveal themselves at the conceptual level of this service. In particular, the activation of parental responsibility will be analyzed. Furthermore, this paper discusses the scope of action for social work and highlights tendencies that indicate that this field of social work conveys aspects of a social infrastructure. This raises questions about the implications for the status of citizenship concerning the users of these services.